Influence of stakeholder partnership on school improvement and performance - Paguyo, Zorayda Salaan (Laoag City : [s.n.], 2016)
This study described the quality of partnership of the internal and external stakeholders of a school, the extent to which the elementary schools in the Division of Ilocos Norte improved from 2011-2015, and how well they performed. School improvement was described along staff development and physical development of the schools. School performance was described in terms of the performance indicators of the DepED and pupil performance in curricular and co-curricular competitions. The relationships among the three variables was also determined. The study used the descriptive method of research utilizing the Input-Process- Output model. Input was the quality of partnership between the internal and external stakeholders of an elementary school, the independent variable; process was school improvement, the moderating variable; and output was pupil performance, the dependent variable. The internal stakeholders were the teachers, school head and parents, while the external stakeholders included the school, home, community and local government unit (LGU). The partnership of these stakeholders was theorized to influence school improvement with regard to staff development and physical facilities development, and the pupil performance of pupils indicated by the performance indicators and different competitions.
Bibliography: pages 102-106.
CHED-La Union
Keywords: Schools -- Administration